2018
DOI: 10.5204/qutlr.v18i1.732
|View full text |Cite
|
Sign up to set email alerts
|

On the Bottle: Health Information, Alcohol Labelling and the WTO Technical Barriers to Trade Agreement

Abstract: Since 2010, the World Health Organization has advocated the use of health information labelling to inform consumers of the health risks related to alcohol consumption. The alcohol industry oscillates between opposing and supporting alcohol labelling. This article reviews the minutes of the meetings of the World Trade Organization’s (‘WTO’s’) Committee on Technical Barriers to Trade (‘TBT’) (from 2010 to the present day) to garner unique insights into the specific features of alcohol health information labellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…It has been suggested that countries considering implementing such measures will need to provide greater justification for these and scientific evidence for their effectiveness, and face pressures to implement less trade‐restrictive measures such as education campaigns. Similar practices have been documented around alcohol labelling 20 …”
Section: Trade Agreements Are Structural Drivers Of Ncdssupporting
confidence: 56%
“…It has been suggested that countries considering implementing such measures will need to provide greater justification for these and scientific evidence for their effectiveness, and face pressures to implement less trade‐restrictive measures such as education campaigns. Similar practices have been documented around alcohol labelling 20 …”
Section: Trade Agreements Are Structural Drivers Of Ncdssupporting
confidence: 56%
“…Similar practices have been documented in reference to alcohol labelling. 18 Since the vast majority of concerns will not escalate to formal disputes 19 , this is a key venue to explore the impact of trade concerns on potential shifts in policy formulation.…”
Section: Reforming Investor-state Dispute Settlementmentioning
confidence: 99%
“…[2][3][4] Analyses have highlighted both the potential positive impacts of trade (for example through greater access to health promoting goods and services), as well as the potential negative impacts including constraints on governments' ability to regulate and the liberalisation of trade in health-harmful commodities. [5][6][7][8][9] Indeed, the global rise in non-communicable diseases (NCDs) as "one of the major challenges for development in the 21st century" 10 is due to a rise in NCD risk factors including tobacco use, harmful use of alcohol, poor physical activity and poor nutrition. 11 Trade agreements have facilitated these NCD risk factors by increasing the volume of health harmful commodity imports, as well as local production, manufacturing and distribution of these products through goods and services liberalisation, provisions that reduce tariffs (ie, border taxes) and the elimination of restrictions on foreign direct investment.…”
Section: Introductionmentioning
confidence: 99%